Assessment of Translational and Interdisciplinary Clinical Research at an Oklahoma Health Sciences Center - Dao, Hanh Dung (J Okla State Med Assoc, 2015)
PURPOSE: In response to National Institutes of Health initiatives to improve translation of basic science discoveries we surveyed faculty to assess patterns of and barriers to translational research in Oklahoma. METHODS: An online survey was administered to University of Oklahoma Health Sciences Center, College of Medicine faculty, which included demographic and research questions. RESULTS: Responses were received from 126 faculty members (24%). Two-thirds spent ≥20% time on research; among these, 90% conduct clinical and translational research. Identifying funding; recruiting research staff and participants; preparing reports and agreements; and protecting research time were commonly perceived as at least moderate barriers to conducting research. While respondents largely collaborated within their discipline, clinical investigators were more likely than basic science investigators to engage in interdisciplinary research. CONCLUSION: While engagement in translational research is common, specific barriers impact the research process. This could be improved through an expanded interdisciplinary collaboration and research support structure.